2019
DOI: 10.1038/s41598-019-45851-3
|View full text |Cite
|
Sign up to set email alerts
|

Versican is crucial for the initiation of cardiovascular lumen development in medaka (Oryzias latipes)

Abstract: Versican is an evolutionary conserved extracellular matrix proteoglycan, and versican expression loss in mice results in embryonic lethality owing to cardiovascular defects. However, the in utero development of mammals limits our understanding of the precise role of versican during cardiovascular development. Therefore, the use of evolutionarily distant species that develop ex utero is more suitable for studying the mechanistic basis of versican activity. We perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 88 publications
1
12
1
Order By: Relevance
“…We have provided the first evidence that laminin restricts heart growth during looping morphogenesis by limiting the number of SHF cells incorporated into the venous pole of the heart. Previous studies have identified roles for ECM components such as Versican and Fibronectin in promoting SHF addition to the arterial pole of the heart [79][80][81][82][83], however we have identified an opposing role for Lamb1a in restricting excessive SHF addition to the venous pole. Highlighting the importance of cell-ECM interactions in the SHF loss of Tbx1, a master regulator of SHF addition, results in reduced expression of Integrin, loss of focal adhesion markers, and impaired filopodia formation in the SHF [84,85].…”
Section: Discussioncontrasting
confidence: 54%
“…We have provided the first evidence that laminin restricts heart growth during looping morphogenesis by limiting the number of SHF cells incorporated into the venous pole of the heart. Previous studies have identified roles for ECM components such as Versican and Fibronectin in promoting SHF addition to the arterial pole of the heart [79][80][81][82][83], however we have identified an opposing role for Lamb1a in restricting excessive SHF addition to the venous pole. Highlighting the importance of cell-ECM interactions in the SHF loss of Tbx1, a master regulator of SHF addition, results in reduced expression of Integrin, loss of focal adhesion markers, and impaired filopodia formation in the SHF [84,85].…”
Section: Discussioncontrasting
confidence: 54%
“…However, as G. holbrooki embryos develop, at later stages, the heart contractions show a more co-ordinated pattern as is also the case for zebrafish embryos [ 16 ], which is linked to a substantial increase in cardiomyocyte numbers [ 51 ]. This is also consistent with observations in medaka [ 27 , 29 ] and mammals including humans [ 52 ].…”
Section: Discussionsupporting
confidence: 93%
“…Although the teleost lineage exhibits morphological evolutionary novelty such as bulbus arteriosus, they express genes that are conserved across vertebrates [ 50 ]. Therefore, fish such as zebrafish [ 18 ] and medaka [ 28 , 29 ] have been used as the model for cardiovascular studies. However, these species do not appear to show cardiac-related sex-specific differences, unlike humans [ 14 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the effects of SNC on the vascular formation and embryonic developments of medaka, we employed epidermal growth factor‐like domain 7 (eg, fl7), a key marker of angiogenic signaling factor. EGFL7 is produced exclusively by vascular endothelial cells, 13 and egfl7 is expressed in vascular endothelial cells during medaka embryogenesis 14 . In addition, e gfl7 is important for regulating tubulogenesis in zebrafish 15 and for controlling vascular patterning and integrity in mice 16 .…”
Section: Introductionmentioning
confidence: 99%